Feminist Tafsir: Makiyyah and Madaniyyah's Significance for 'Ulumul Qur'an in the Thought of Husein Muhammad - Sartika, Ela (UIN Sunan Gunung Djati Bandung, 2024)
The grand theory of makiyyah and madaniyyah according to classical scholars is seen from three aspects, namely time, place, and object of the speaker. However, Husein Muhammad perspektive makiyyah and madaniyyah from the aspect of time only. This view stems from Husayn's definition of the Qur'an as a guide that will always be relevant to human life. Through the Makiyyah and Madnaiyyah theories, he shows an interpretation that is not gender biased but has implications for the 'Ulumul Qur’an theory. This problem raises two questions about the concept of makiyyah and madaniyyah according to Husein Muhammad, and what are the implications of his views on the 'ulumul Qur'an. The results of this study indicate that Husein Muhammad has the view that makiyyah and madaniyyah are influenced by the social reality of Arab society. The Makiyyah verses show a universal meaning while the madaniyyah verses show a partikular meaning so that it has implications for the 'ulumul Qur'an aspect, namely the mansukh, muhkam, and mutasyabih texts.